2023
DOI: 10.1002/anie.202217210
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms and Synthetic Strategies in Visible Light‐Driven [2+2]‐Heterocycloadditions

Abstract: The synthesis of four membered heterocycles usually requires multi-step procedures and prefunctionalized reactants. A straightforward alternative is the photochemical [2+2]-heterocycloaddition between an alkene and a carbonyl derivative, conventionally based on the photoexcitation of this latter. However, this approach is limited by the absorption profile of the carbonyl, requiring in most of the cases the use of high-energy UV-light, that often results in undesired side reactions and/or the degradation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 148 publications
0
24
0
Order By: Relevance
“…Photochemistry enables the generation of radical species under mild conditions without the need for classical toxic or expensive radical precursors such as organotin reagents or samarium. Apart from single carbon radicals, which have been intensively studied, the reactivity of 1,2 biradicals has recently been the focus of strong interest, especially in the context of the excitation of conjugated π-carbonyl systems through energy transfer catalysis (Scheme A). , In contrast, the generation of nonconjugated 1,n biradicals through the homolytic cleavage of C–C bonds in carbocycles remains challenging due to the larger bond dissociation energy of a σ C–C bond compared to a π bond. The 1,n biradicals can then be applied in further cyclizations or ring expansions to rapidly increase the complexity of small molecules …”
Section: Introductionmentioning
confidence: 99%
“…Photochemistry enables the generation of radical species under mild conditions without the need for classical toxic or expensive radical precursors such as organotin reagents or samarium. Apart from single carbon radicals, which have been intensively studied, the reactivity of 1,2 biradicals has recently been the focus of strong interest, especially in the context of the excitation of conjugated π-carbonyl systems through energy transfer catalysis (Scheme A). , In contrast, the generation of nonconjugated 1,n biradicals through the homolytic cleavage of C–C bonds in carbocycles remains challenging due to the larger bond dissociation energy of a σ C–C bond compared to a π bond. The 1,n biradicals can then be applied in further cyclizations or ring expansions to rapidly increase the complexity of small molecules …”
Section: Introductionmentioning
confidence: 99%
“…31 The triplet state energy transfer (EnT) catalysis has been recently employed for diverse organic transformations and reviewed as well. 23,[32][33][34][35][36][37][38][39][40] The last review focused on arene-alkene cycloaddition was reported in 2016. 3 The modern visible-light mediated EnT dearomative cycloaddition has been advanced since 2018 and is rapidly developing en route to becoming the cornerstone of synthetic methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic strategies, exploiting exciplex manifolds in [2 + 2]heterocycloadditions mediated by visible light and involving carbonyl partners, has been reviewed by Franceschi et al in early 2023 therefore it will not be the subject of this work. [6] Concerning the classification of the reactions presented according to a domino, tandem or a multicomponent process, we employed the definition used in the original paper. For a more detailed definition of domino/tandem reactions in organic synthesis see the paper from Tietze.…”
Section: Introductionmentioning
confidence: 99%